Gas-phase chemistry of molecular containers. (24th June 2014) - Qi, Zhenhui; Heinrich, Thomas; Moorthy, Suresh; Schalley, Christoph A.
Abstract : The use of mass spectrometry for the investigation of supramolecular capsules and containers in solution and the gas-phase is reviewed. Abstract : The remarkable technical advances in mass spectrometry during the last decades, including soft ionisation techniques, the coupling of electrospray ionisation to flow reactors, and the broad scope of tandem mass spectrometric experiments applicable to mass-selected ions allow investigating the chemistry of molecular capsules in solution as well as in the absence of any environment. With these methods, mass spectrometry is capable of answering many questions starting from providing analytical characterisation data (elemental composition, stoichiometry, etc. ) to structural aspects (connectivities, positions of building blocks in supramolecular complexes) and to the examination of solution and gas-phase reactivity including reactions inside molecular containers. The present article reviews this work with a focus rather on the chemical questions that can be answered than on the technical specialities of (tandem) mass spectrometry.